Evaluation of Anti biofilm and Antibiotic Potentiation Activities of Silver Nanoparticles against Some Nosocomial Pathogens: Nanosilver antibiofilm activity - Ebrahimi, Azizollah; Lotfalian, Sharareh; Jafferi, Hossein; Habibian, Saied (Iranian Journal of Pharmaceutical Sciences, 2018)
Nowadays silver nanoparticles (AgNPs) are used as antimicrobial due to its well known physical, chemical, and biological properties. A large collection of bacterial cells adhering to a surface is called bacterial biofilm. Exposure to silver nano particles (AgNPs) may prevent colonization of new bacteria onto the biofilm. In the present work, we have investigated whether the biofilm formation of some hospital isolates of pathogenic bacteria could be influenced by AgNPs. Also we examined the susceptibility of the isolates to some antibiotics in combination with AgNPs. Standard strains of Pseudomonas aeruginosa, Acinetobacter baumannii, Enterococcus faecalis and Staphylococcus aureus, in addition to nine hospital isolates for each species were used. Tube double serial dilution method for determination of MIC of AgNPs against isolates was performed. Biofilm formation was evaluated by end smooth 96 cells micro titer plates. A disc diffusion method was used to assay the various antibiotics and combinations for bactericidal activity against the isolates. Mean MICs of AgNPs for Ps. aeruginosa, A. baumannii, E. faecalis and S. aureus were 3.125, 6.25, 6.25 and 12.5 ug/mL. , respectively. AgNPs exhibited more than % 90 inhibitory effect on biofilm formation of the examined species. The results indicated that AgNPs have strong anti bacterial and anti biofilm activity against the examined pathogens. Synergistic effects of AgNPs in combination with gentamicin, kanamycine, cephalosporin and penicillin were observed in different cases. Ps. aeruginosa and S. aureus showed more sensitivity (increase in fold) to examined antibiotics plus AgNPs compared to A. baumannii and E. faecalis. Our results demonstrated that AgNPs showing promising anti biofilm activity on hospital isolates of Ps. aeruginosa, A. baumannii, E. faecalis and S. aureus. The study also demonstrated a possible combination of examined antibiotics with AgNPs which concluded as synergism.